Reinterpretasi Teater Tradisi Dalam Perspektif Patronase - Heny Purnomo (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2022)
Traditional art theatre that is owned and attached to a community can be used to understand the culture of a society. This is true because traditional arts and theater reflect the personality and way of life of the broader community. Traditional theatrical productions that are held live and move from one location to another (tobong) are becoming increasingly rare and are currently on the verge of extinction. Additionally, every performance is always in competition with other arts that have been transformed by other technological media television. Many forms of presentation produced using stage visuals were influenced by ludruk tobong, which had its peak in the 1970s and 1980s. Ludruk Tobong, a traditional populist-based theater, was born and raised in a society that has served as its primary patron. Every staging of a play incorporates "actors and patrons" as a representation of life, and this is also true of the ludruk tobong performance. When entertainment in multiple media can alienate an audience, the ludruk tobong packaging is now regarded as outmoded and does not offer market benefits, making it more difficult to carry out regeneration, which causes a gradual fall in both supporters and perpetrators. It's interesting to investigate social dynamics that affect the continued existence of traditional populist arts or theater through a patronage-based reinterpretation. This qualitative study aims to describe various supporting factors and explain the reinterpretation and patronage perspectives in ludruk tobong performances as traditional theater. To analyze the results of the study, the concept of traditional art and the analogy of Goffman's performance or dramaturgy were used as well as the concept of patronage and various other concepts that were also supported by the results of interviews in the field.